2020
DOI: 10.1212/wnl.0000000000010086
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of prion diseases by RT-QuIC results in improved surveillance

Abstract: Objective:We present the National Prion Disease Pathology Surveillance Center’s (NPDPSC) experience using cerebrospinal fluid (CSF) real time quaking induced conversion (RT-QuIC) as a diagnostic test, examine factors associated with false negative RT-QuIC results, and investigate RT-QuIC’s impact on prion disease surveillance.Methods:Between May 2015-April 2018, the NPDPSC received 10,498 CSF specimens that were included in the study. Sensitivity and specificity analyses were performed using 567 autopsy verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
126
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(141 citation statements)
references
References 11 publications
13
126
2
Order By: Relevance
“…Franceschini et al, [31] in a large cohort of cases with disease subtype classification, found comparable levels of sensitivities in the three most common subtypes, namely MM(V)1, VV2 and MV2K, but confirmed the findings of reduced sensitivity of IQ CSF RT-QuIC in both MM2 subtypes (i.e., MM2C and MM2T or sFI). Similarly, Rhoads and co-workers recently reported that atypical sporadic prion disease subtypes (i.e., sFI, VPSPr, sCJD VV1, and sCJD MM2C) are more likely to have false negative RT-QuIC results [72].…”
Section: Current Unsolved Questions and Potential Limitations Is Priomentioning
confidence: 86%
See 2 more Smart Citations
“…Franceschini et al, [31] in a large cohort of cases with disease subtype classification, found comparable levels of sensitivities in the three most common subtypes, namely MM(V)1, VV2 and MV2K, but confirmed the findings of reduced sensitivity of IQ CSF RT-QuIC in both MM2 subtypes (i.e., MM2C and MM2T or sFI). Similarly, Rhoads and co-workers recently reported that atypical sporadic prion disease subtypes (i.e., sFI, VPSPr, sCJD VV1, and sCJD MM2C) are more likely to have false negative RT-QuIC results [72].…”
Section: Current Unsolved Questions and Potential Limitations Is Priomentioning
confidence: 86%
“…Results were comparable between the groups, with only a slightly higher sensitivity in GSS compared to FFI and gCJD (90% vs. 83.3%). In contrast, other groups, using different protocols, consistently reported a reduced sensitivity of RT-QuIC in FFI (0-57%), and GSS (0-50%) compared with gCJD (83.3-100%) [12,22,30,31,72]. Moreover, RT-QuIC gave positive results in one asymptomatic E200K carrier, who did not develop the disease after a 1-year follow-up [88].…”
Section: Current Unsolved Questions and Potential Limitations Is Priomentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to specificity, the ideal biomarker is highly sensitive to support early diagnosis, demonstrates a sufficient dynamic range to evaluate clinically relevant quantitative changes with longitudinal studies, and can be measured in easily accessible biofluid or tissue specimens. Prion RT-QuIC assays have been successfully implemented for the diagnosis of prion diseases, with RT-QuIC evaluation of cerebrospinal fluid (CSF) currently being used as part of the diagnostic work-up for sporadic Creutzfeldt-Jakob disease (sCJD) [ 50 , 51 , 52 , 53 , 54 ]. In addition, prion RT-QuIC assays have been adapted for a range of diagnostically relevant human biospecimens including CSF [ 48 , 53 , 55 , 56 ], olfactory mucosa [ 57 ], eyes [ 58 ], and skin [ 59 , 60 ].…”
Section: Rt-quic Assays As Diagnostic Toolsmentioning
confidence: 99%
“…From a diagnostic viewpoint, RT-QuIC is particularly efficient at amplifying prion sub-infectious doses in sample biopsies from the skin (Orru et al, 2017), olfactory mucosa (Orru et al, 2014), urine, saliva (Henderson et al, 2015), blood (Elder et al, 2013), and CSF (McGuire et al, 2012). The second generation of RT-QuIC specially designed for prion detection in the CSF achieved >95% sensitivity and 100% specificity (Orru et al, 2015a), with a good interlaboratory reproducibility, thus opening new avenue for ante-mortem diagnosis of CJD (Rhoads et al, 2020). CSF-based RT-QuIC is now considered as the most powerful versatile technique for diagnosing CJD.…”
Section: The Rt-quic Assaymentioning
confidence: 99%